Rancangan Paket Media Edukasi Pencegahan Stunting Berbasis Teknologi dan Kearifan Lokal: Design of Stunting Prevention Education Media Package Based on Technology and Local Wisdom - Nurcahyani, Lia; Widiyastuti, Dyah; Estuti, Wiwit; Iman, Arief Tarmansyah; Fitrianingsih, Yeni; Hafid, Fahmi (Universitas Airlangga, 2024)
Background: Stunting leads to increased morbidity and mortality among children. To accelerate stunting reduction, family assistance teams support at-risk families, requiring engaging and accessible educational resources. However, existing educational media materials are fragmented and lack a comprehensive approach, resulting in gaps during family assistance sessions. To improve accessibility and efficacy, a comprehensive, technology-based educational tool is necessary. Objectives: To develop a Stunting Prevention Education Media Package (PaSti PenTing) based on technology and local wisdom. Methods: This study used a Research and Development approach conducted in Cirebon City. The stages included the formulation of basic concepts, and in-depth interviews with experts, namely the Chairman of the Central Board of the Indonesian Midwives Association, the Head of the Cirebon City Health Office, the Head of the Cirebon City Women's Empowerment, Child Protection, Population Control and Family Planning Office and lecturers with S3 backgrounds. These interviews provided input related to the materials used for designing the PaSti PenTing. The research instrument uses in-depth interview guidance and data analysis was carried out using content analysis. Results: Based on expert input, the PaSti PenTing design was developed. The main menu consists of an introduction and a menu for target groups (teenagers, brides-to-be, pregnant women, postpartum mothers, and toddlers). Each menu contains educational materials. Conclusions: PasTi PenTing is a comprehensive media that can be used by the assistance team and families at risk of stunting to improve knowledge, attitudes, and behaviors in stunting prevention.